Novel Strategies and Approaches in Hypertension Therapy - Uzun, Hafize; Atukeren, Pnar (Bentham Science Publishers, 2019)
INTRODUCTION:Hypertension has become a major public health problem in the last few decades. High blood pressure is a serious risk factor for premature cardiovascular disease and end-organ damage including left-ventricular hypertrophy and congestive heart failure, which in turn increases the risk of cardiovascular morbidity and mortality.While studies of hypertension have been performed worldwide in a variety of epidemiological settings such as diabetes, renal function, obesity and thyroid disorders, there is a need to identify appropriate treatment strategiesNovel Strategies and Approaches in Hypertension introduces the reader to different aspects of hypertension treatment (environmental and occupational factors and different clinical settings that can trigger the disease). The book also covers special topics related to the use of new diagnostic biomarkers for hypertension patients, as well as endocrine and nutrition-focused approaches to treat the condition.This reference book will be useful for medical professionals involved in the management and care of patients affected with hypertension.[Series Introduction]Frontiers in Hypertension presents reference works, textbooks and monographs on both fundamental and advanced topics related to the pathophysiology, diagnosis and treatment of hypertension. The series is essential reading for medical students and professionals involved in hypertension and allied subspecialty treatment programs.